2011
DOI: 10.1002/hyp.8089
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating landscape features to obtain an object‐oriented landscape drainage network representing the connectivity of surface flow pathways over rural catchments

Abstract: Abstract:A topological representation of a rural catchment is proposed here in addition to the generally used topographic drainage network. This is an object-oriented representation based on the identification of the inlets and outlets for surface water flow on each farmer's field (or plot) and their respective contributing areas and relationships. It represents the catchment as a set of independent plot outlet trees reaching the stream, while a given plot outlet tree represents the pattern of surface flow rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
(64 reference statements)
1
33
0
Order By: Relevance
“…The runoff connectivity is controlled by K sat patterns (Harel & Mouche, ), as well as by macrotopography, for example, berms, embankments, ditches (Levavasseur, Bailly, Lagacherie, Colin, & Rabotin, ), hedges (Gascuel‐Odoux et al . , ), detention ponds (Chrétien, Gagnon, Thériault, & Guillou, ), and by microtopography resulting from tillage or wheel tracks (FpMasters, Rohde, Gurner, & Reid, ). The runoff dynamic, that is, the flow discharge, is controlled by the slope, the surface roughness and the hydraulic resistance expressed by the Manning's coefficient ( n ).…”
Section: Introductionmentioning
confidence: 99%
“…The runoff connectivity is controlled by K sat patterns (Harel & Mouche, ), as well as by macrotopography, for example, berms, embankments, ditches (Levavasseur, Bailly, Lagacherie, Colin, & Rabotin, ), hedges (Gascuel‐Odoux et al . , ), detention ponds (Chrétien, Gagnon, Thériault, & Guillou, ), and by microtopography resulting from tillage or wheel tracks (FpMasters, Rohde, Gurner, & Reid, ). The runoff dynamic, that is, the flow discharge, is controlled by the slope, the surface roughness and the hydraulic resistance expressed by the Manning's coefficient ( n ).…”
Section: Introductionmentioning
confidence: 99%
“…Wichmann et al, 2008). In the end, this approach is somewhat comparable to the study by Gascuel-Odoux et al (2011) who use a high-resolution DEM for overland flow routing and a map of agricultural fields which they link through flowpaths in order to create an object-oriented (rather than a pixel-oriented) drainage network. The rockfall production rates forming the basis of regionalisation and up-scaling currently depend on the surface area of the source cells in the DEM only.…”
Section: Comprehensive Discussion Of the Approachmentioning
confidence: 97%
“…Not all cattle farmers have performed the work necessary to exclude cattle. In addition, even though much of the bocage is preserved in Moulinet, and grasslands cover much of its area, a small percentage of the catchment (3% in 2008) occupied by crop fields is nonetheless connected to the stream (Gascuel‐Odoux et al, ). In the same catchment, Vongvixay () analysed SS data (from October 2005 to September 2008) and concluded that soil erosion from hillslopes was another source of SS during certain storm events, especially in autumn and spring.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, grasslands and woodlands covered about 50% of the catchment. Croplands (mostly wheat and maize), covering 40% of the catchment, were located mainly in upslope and midslope areas (Gascuel‐Odoux et al, ; Figure ). In the Kervidy‐Naizin catchment, agriculture is dominated by intensive production of cattle (1.2 cows ha −1 UAA, mostly fed indoors) and pigs (9.2 pigs ha −1 UAA).…”
Section: Methodsmentioning
confidence: 99%